Developing connection in positive youth development: leadership learning through mentoring process among youth leaders in Malaysia - Arshad, Mohd Mursyid; Ismail, Ismi Arif; Suandi, Turiman; Omar, Zoharah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Youth leadership development is one of the important agenda needed in the country's development agenda as outlined in the ‘Transformasi Nasional 2050’ (TN 50) (Najib Razak, 2017). The involvement of young leaders can be strengthened through wider exposure and professional training, including via mentoring that enhances Positive Youth Development among youths. Thus, mentoring has the potential in providing that kind of learning process. Therefore, this study was conducted to explore the process of mentoring towards PYD and how protégé enhanced connection in the mentoring process? Therefore, the question addressed in this paper is how mentoring contributes to the process of connection building to youth to develop their leadership ability and eventually fulfilling the overall PYD needs.